Cytomegalovirus: an unlikely ally in the fight against blood cancers?. (21st September 2018) - Bigley, A B; Baker, F L; Simpson, R J
Summary: Cytomegalovirus (CMV) infection is a potentially fatal complication in patients receiving haematopoietic stem cell transplantation (HSCT), but recent evidence indicates that CMV has strong anti-leukaemia effects due in part to shifts in the composition of natural killer (NK) cell subsets. NK cells are the primary mediators of the anti-leukaemia effect of allogeneic HSCT, and infusion of allogeneic NK cells has shown promise as a means of inducing remission and preventing relapse of several different haematological malignancies. The effectiveness of these treatments is limited, however, when tumours express human leucocyte antigen (HLA)-E, a ligand for the inhibitory receptor NKG2A, which is expressed by the vast majority of post-transplant reconstituted and ex-vivo expanded NK cells. It is possible to enhance NK cell cytotoxicity against HLA-E pos malignancies by increasing the proportion of NK cells expressing NKG2C (the activating receptor for HLA-E) and lacking the corresponding inhibitory receptor NKG2A. The proportion of NKG2C pos /NKG2A neg NK cells is typically low in healthy adults, but it can be increased by CMV infection or ex-vivo expansion of NK cells using HLA-E-transfected feeder cells and interleukin (IL)-15. In this review, we will discuss the role of CMV-driven NKG2C pos /NKG2A neg NK cell expansion on anti-tumour cytotoxicity and disease progression in the context of haematological malignancies, and explore the possibility of harnessing NKG2C pos /NKG2A neg NK cells for cancer immunotherapy. Graphical Abstract: